2021
DOI: 10.7554/elife.70436
|View full text |Cite
|
Sign up to set email alerts
|

STING mediates immune responses in the closest living relatives of animals

Abstract: Animals have evolved unique repertoires of innate immune genes and pathways that provide their first line of defense against pathogens. To reconstruct the ancestry of animal innate immunity, we have developed the choanoflagellate Monosiga brevicollis, one of the closest living relatives of animals, as a model for studying mechanisms underlying pathogen recognition and immune response. We found that M. brevicollis is killed by exposure to Pseudomonas aeruginosa bacteria. Moreover, M. brevicollis expresses STING… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…It has been reported that CnpB could degrade nanoRNAs (RNA oligos of ≤5 nucleotides) ( Postic et al., 2012 ), and even hydrolyze c-di-GMP at a lower rate than it did on c-di-AMP ( Bowman et al., 2016 ). In S. aureus , it was reported that the cytoplasmic DHH/DHHA1 phosphodiesterase PDE (Pde2) preferentially converts linear 5-phosphadenylyl-adenosine (pApA) to AMP ( Woznica et al., 2021 ). Moreover, pApA is involved in a feedback inhibition loop that limits the membrane DHH/DHHA1 phosphodiesterase (GdpP) dependent c-di-AMP hydrolysis ( Bowman et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CnpB could degrade nanoRNAs (RNA oligos of ≤5 nucleotides) ( Postic et al., 2012 ), and even hydrolyze c-di-GMP at a lower rate than it did on c-di-AMP ( Bowman et al., 2016 ). In S. aureus , it was reported that the cytoplasmic DHH/DHHA1 phosphodiesterase PDE (Pde2) preferentially converts linear 5-phosphadenylyl-adenosine (pApA) to AMP ( Woznica et al., 2021 ). Moreover, pApA is involved in a feedback inhibition loop that limits the membrane DHH/DHHA1 phosphodiesterase (GdpP) dependent c-di-AMP hydrolysis ( Bowman et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its structure has significantly changed and evolved from unicellular organisms to vertebrates [46]. Before the existence of IFNs system in vertebrates, STING was already playing a central role in antipathogen immunity in unicellular protists [47] and invertebrates species [48,49]. In these organisms STING executes its immune function by inducing autophagy and activation of NF-ĸB signaling (a homolog of NF-ĸB in protists) [50], the two downstream pathways thought to be associated with ancestral STING function.…”
Section: Sting Gene and Protein: Evolutionary Conservationmentioning
confidence: 99%
“…Roles for TLR- or cGAS-STING-induced activation of NF-κB in basal immunity have been suggested by experiments in sea anemones, corals, hydra, sponges, and choanoflagellates [ 4 9 ]. Herein, we discuss some of the knowledge about the TLR and cGAS-STING pathways and roles that they may play in invertebrate immunity, as well as exciting information about approaches to antimicrobial immunity that may be gained from further study of basal immunity and its regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Margolis and colleagues [ 8 ] have shown that bacterial infection or treatment with a 2′3′ cGAMP mimetic can activate an antipathogen gene expression response in Nematostella , which also leads to up-regulation of nuclear NF-κB expression. Moreover, STING has been shown to play a role in an antibacterial response in some choanoflagellates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%